2021
DOI: 10.1109/access.2021.3103843
|View full text |Cite
|
Sign up to set email alerts
|

A Probabilistic Broadcasting Scheme for Emergent Message Dissemination in Urban Internet of Vehicles

Abstract: The Internet of Vehicles(IoV) has attracted increasing attentions for its potential of enhancing driving safety and traffic efficiency. The Multi-hop broadcast is one of the important techniques for timesensitive data dissemination especially in emergent cases. As a result, how to wisely select the next-hop during Multi-hop routing plays an important role for performance improvement in IoV as well as dependent applications. Nevertheless, in view of the high mobility, frequent changing topology and complicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The dedicated spectrum for this protocol is 75 MHz in the range of 5.850-5.925 GHz [54], [55]. One of the main problems using IEEE 802.11p technology in emergency traffic situations is broadcast storms, which have been addressed in the literature [56], [57], [58], [59], and [60] using various mechanisms. The clustering technique was introduced in [56], [58], and [60] to reduce broadcast storms and disseminate ESMs by choosing a forwarder that has higher compatible interests with other vehicles in [56].…”
Section: A Traditional Ieee 80211p Protocol-enabled Esms Disseminationmentioning
confidence: 99%
See 1 more Smart Citation
“…The dedicated spectrum for this protocol is 75 MHz in the range of 5.850-5.925 GHz [54], [55]. One of the main problems using IEEE 802.11p technology in emergency traffic situations is broadcast storms, which have been addressed in the literature [56], [57], [58], [59], and [60] using various mechanisms. The clustering technique was introduced in [56], [58], and [60] to reduce broadcast storms and disseminate ESMs by choosing a forwarder that has higher compatible interests with other vehicles in [56].…”
Section: A Traditional Ieee 80211p Protocol-enabled Esms Disseminationmentioning
confidence: 99%
“…[60] outperformed [58] by examining the link stable estimation parameter and achieving improved results. The protocol in [57] strengthened reliability by evaluating each vehicle's transmission probability concerning distance, packet reception ratio, and link availability metrics. The vehicle with the highest value forwards the ESM, with other vehicles as backups in case of failure.…”
Section: A Traditional Ieee 80211p Protocol-enabled Esms Disseminationmentioning
confidence: 99%
“…Li et al 54 proposed a mathematical model for the efficient emergent data propagation (EDP) in IoV. The authors suggested a probabilistic method for choosing the proper node as a relay node in a multi‐hop discipline of data propagation.…”
Section: Analysis Of Data‐centric Approaches In Iovmentioning
confidence: 99%
“…In such a large-scale, heterogeneous, complex network, the design of a reliable and efficient routing strategy is of great necessity but quite challenging [3][4][5]. Therefore, the study of routing strategies has long been a hot topic in the research field of intelligent vehicular networks [6][7][8].…”
Section: Introductionmentioning
confidence: 99%